The impact of oil price changes on efficiency of banks: An application in the Middle East oil exporting countries using SORM-DEA - Kaffash, Sepideh; Aktas, Emel; Tajik, Mohammad (EDP Sciences, 2020)
This paper presents a novel application of Data Envelopment Analysis (DEA) to analyze the impact of oil price changes on the efficiency of banks. Factors that affect the efficiency of banks have been of interest to researchers in various geographical regions. With a special focus on oil price changes, we investigate the determinants of bank efficiency in the Middle Eastern Oil-Exporting (MEOE) countries where macro-financial conditions are substantially affected by swings in oil prices. Our analysis consists of two stages: (i) measuring the efficiency scores of banks using the Semi-Oriented Radial Measure (SORM) DEA model, (ii) investigating the impact of alternative indicators of oil prices on the estimated efficiency scores after controlling for key bank-specific and country-specific variables. The analysis is based on an un-balanced panel data of banks operating in the Middle Eastern Oil-Exporting countries over the period of 2001–2011. Our findings reveal that oil price changes affect the efficiency of banks in the MEOE countries through both direct and indirect channels. In addition, we find that Islamic banks in the region are less responsive to oil price changes than commercial and investment banks.
Keywords: Data Envelopment Analysis; bank efficiency; oil price changes; the Middle Eastern oil-exporting countries